An overview on trace CO2 removal by advanced physisorbent materials. (1st February 2020) - Khraisheh, Majeda; Mukherjee, Soumya; Kumar, Amrit; Al Momani, Fares; Walker, Gavin; Zaworotko, Michael J.
Abstract: This review paper focuses on various gas processing technologies and materials that efficiently capture trace levels of carbon dioxide (CO2 ). Fundamental separation mechanisms such as absorption, adsorption, and distillation technology are presented. Liquid amine-based carbon capture (C-capture) technologies have been in existence for over half a century, however, liquid amine capture relies upon chemical reactions and is energy-intensive. Liquid amines are thus not economically viable for broad deployment and offer little room for innovation. Innovative C-capture technologies must improve both the environmental footprint and cost-effectiveness. As a promising alternative, physisorbents have many advantages including considerably lower regeneration energy. Generally, existing classes of physisorbent materials, such as metal-organic frameworks (MOFs) and zeolites are selective toward C-capture. However, their selectivity is currently not high enough to remove trace levels (e.g., 1%) of CO2 from various natural gas process streams. This review summarizes the current advancements in physisorbent materials for CO2 capture. Here, key performance parameters needed to select the most suitable candidate are highlighted. Furthermore, this review discusses the scope for the development of better performing CO2 selective physisorbents from both environmental and economic perspectives. In addition, hybrid ultra microporous materials (HUMs), characterized mainly by ultra-micro pores (<0.7 nm), are discussed in reference to C-capture. Various characteristics of HUMs result in high selectivity and applicability in difficult separations such as the gas sweetening and C-capture from complex humid mixed gas streams. Graphical abstract: Image 1 Highlights: Materials used to capture traces of CO2 from natural gas processes were reviewed. Fundamental separation mechanisms have been described and compared. Current state of the art physisorbent materials for CO2 capture were summarized. Recently developed Ultramicroporous Materials for CO2 capture were presented. Ultra-micro pores materials have high selectivity for trace impurities CO2 removal from gas.